Digitalization in Supply Chain Management - Khunteta, Tanmay; Jirsák, Petr; Martínez, Felipe; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
In today's era of modernization and digitization, Supply chain management is going to play a vital role in digital development. This thesis investigates the significant impact of digitalization on SCM, and the digitization in the transport system, undergoing with its current analysis and future possibilities. It explores how technology is impacting the SCM and parallel enhancing the business opportunity and giving an authentic solution from start point to the end users.
Vedoucí práce: Petr Jirsák
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses